Selecting Benchmarking Partners Using Analytical Hierarchy Process Approach - Sari Wulandari; Ardian Cahya Utama; Muhammad Arfidh (International Journal of Innovation in Enterprise System, 2020)
Benchmarking is a method to improve performance and improve company competitiveness. Thismethod has been commonly practiced by large companies and has recently been extended tosmall and medium enterprises (SMEs). However, the implementation between large and SMEsis very different. These differences are debated as an impact of company characteristics,specifically differences in the ability to develop and improve business. Typical SMEs face toughchallenges to overcome their resource constraints. This limitation affects the decisions of SMEsin choosing their comparison partners. This research was conducted to fill the research gapregarding the use of the Benchmarking method and the AHP approach to SMEs, especially indetermining Benchmark partners using the AHP approach. The use of benchmarking and AHPis illustrated by using SME objects that are engaged in the fashion sector, namely UKMCotton.Go. The problem faced by UKM Cotton.Go is marketing communication that is noteffective in creating sales so it needs to be determined benchmarking partner in makingimprovements to marketing communication. The use of AHP in determining benchmark partnershelps SMEs to find out which benchmark partners have the best marketing communicationperformance.